2015
DOI: 10.5194/isprsarchives-xl-7-w3-157-2015
|View full text |Cite
|
Sign up to set email alerts
|

NDVI dynamics of the taiga zone in connection with modern climate changes

Abstract: ABSTRACT:This research is dedicated to the investigation of the relations between the XXI century climate changes and Normalized Difference Vegetation Index (NDVI) variability of the taiga zone. For this purposes was used the observations of vegetation variability on the test area located nearby Syktyvkar city (Komi Republic, Russia), 16-day averages of NDVI data derived from TERRA/MODIS space imagery (spatial resolution is about 250 meters), and the air temperature and precipitation observations from Syktyvka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…et al, 2010). Previous stages of our study (Bobkov A. et al, 2015;Tsepelev V. et al, 2015) demonstrated that this relationship appears more clearly for shrub vegetation cover during the spring and summer growing seasons. Obtained result was verified at the ground test plots.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…et al, 2010). Previous stages of our study (Bobkov A. et al, 2015;Tsepelev V. et al, 2015) demonstrated that this relationship appears more clearly for shrub vegetation cover during the spring and summer growing seasons. Obtained result was verified at the ground test plots.…”
Section: Introductionsupporting
confidence: 58%
“…Currently, we have used Version 6 of the MODIS NDVI data (K. Didan, 2015) instead of previously used Version 5. The seasonal NDVI graphs that were produced according to new data version differ slightly from graphs that were produced in our previous studies (Bobkov A. et al, 2015). Analysis of these graphs shows that autumn season temperature trend data coincide with NDVI trend data and could be also applicable for the study of climate change (Table 1).…”
Section: Trendsmentioning
confidence: 89%
See 1 more Smart Citation
“…Changes in vegetation productivity are mainly determined by climate change [62,63]. Bobkov et al [64] reported that there was a statistically positive correlation between NDVI and spring and autumn temperatures of various vegetation types in the experimental area. Coniferous forests, that is, pine forests on poor soils, have the weakest correlation, and grassland and marsh are the most relevant.…”
Section: Discussionmentioning
confidence: 93%